2011
DOI: 10.1002/ibd.21418
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and adverse events in children and young adults undergoing tacrolimus therapy for steroid-refractory colitis

Abstract: Tacrolimus is useful as induction therapy in pediatric patients with corticosteroid-refractory colitis and side effects are generally mild and reversible. Despite these findings, many patients develop exacerbations of colitis upon transition to maintenance therapies. The long-term colectomy rate in this challenging population remains ≈60% over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Thus far, several uncontrolled (9,14,15,17,19) and two placebo-controlled studies (13,18) have demonstrated that tacrolimus can induce remission in both adults (9, 13-15, 17, 18) and children (19). Another calcineurin inhibitor, CsA, is also highly active (60% to 80%) in patients with UC whose disease fails to respond to intravenous corticosteroid therapy (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, several uncontrolled (9,14,15,17,19) and two placebo-controlled studies (13,18) have demonstrated that tacrolimus can induce remission in both adults (9, 13-15, 17, 18) and children (19). Another calcineurin inhibitor, CsA, is also highly active (60% to 80%) in patients with UC whose disease fails to respond to intravenous corticosteroid therapy (20).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CsA is known to be associated with many adverse effects, such as infections, renal dysfunction, hypertension and neurological toxicity (6). Although similar adverse events, including tremors, hyperglycemia, nephrotoxicity and infection, are observed in association with tacrolimus therapy, these effects are generally mild and reversible (19)(20)(21); thus, tacrolimus can be safely administered on a long-term basis. Yamamoto et al investigated the efficacy of tacrolimus as maintenance therapy for patients with refractory UC and suggested that the administration of tacrolimus with low trough levels (5 to 10 ng/mL) as maintenance therapy may represent an alternative therapy for UC patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness data were drawn from a number of sources including RCTs and non-randomised studies. 49,[87][88][89][90][91][92][93][94][95][96][97][98][99] The effectiveness of IFX in inducing and maintaining response and remission was based on the results of the ACT1 and ACT2 studies. 49 The rate of developing colorectal cancer was derived from an observational study.…”
Section: Assessment Of Cost-effectivenessmentioning
confidence: 99%
“…Ninety-three percent of patients were discharged without undergoing surgery and the probability of avoiding colectomy after starting tacrolimus was 40% at 26 months. 42 We report the published experience from our group of 6 pediatric steroidrefractory patients with moderate/ severe UC who were treated with tacrolimus (0.1 mg/kg/dose twice daily) achieving blood levels between 7 and 10 ng/mL. Response was evaluated by using PUCAI scores, and all patients responded within 1 to 2 weeks.…”
Section: Tacrolimusmentioning
confidence: 99%